2021
DOI: 10.1111/bor.12541
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene–Holocene pedogenesis and palaeoclimate in western Asia from palaeosols of the Central Iranian Plateau

Abstract: The Late Pleistocene and Holocene in western Asia is characterized by frequent, millennial-scale, high-amplitude environmental climatic changes. However, little is known about palaeoclimate conditions on the arid Central Iranian Plateau and knowledge of palaeosols and past phases of pedogenesis in relation to climatic events is scarce. Nevertheless, these palaeosols contain important information on the Last Glacial-Interglacial cycle and Holocene climate and environmental changes in the region. Three represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…No data is available for the timing of fan deposition and abandonment in western Afghanistan. However, studies in eastern Iran revealed that there was a period of intense fan aggradation between 60 and 40 ka in the region (Walker and Fattahi, 2011;Rashidi et al, 2021). On the other hand, loess deposits have filled the plains of the region (Bohanon and Lindsay, 2007).…”
Section: Soil and Landscape Evolution Of The Herat Plainmentioning
confidence: 99%
“…No data is available for the timing of fan deposition and abandonment in western Afghanistan. However, studies in eastern Iran revealed that there was a period of intense fan aggradation between 60 and 40 ka in the region (Walker and Fattahi, 2011;Rashidi et al, 2021). On the other hand, loess deposits have filled the plains of the region (Bohanon and Lindsay, 2007).…”
Section: Soil and Landscape Evolution Of The Herat Plainmentioning
confidence: 99%